Alokasi Waktu dan Kontribusi Perempuan dalam Ketahanan Ekonomi Keluarga di Desa Warnasari Kecamatan Melaya Kabupaten Jembrana - Ni Putu Ayu Meliana Putri; Luh Indrayani (Ekuitas: Jurnal Pendidikan Ekonomi, 2026)
This study aimed to analyse women’s time allocation and their contribution to family economic resilience in Warnasari Village, Melaya District, Jembrana Regency. Rising living costs had created financial pressure on households, and reliance on a single income had become insufficient. This situation encouraged women to undertake dual roles in their daily lives in order to support their families’ economic needs. The approach used was a qualitative descriptive approach with a case study. Data were collected through in-depth interviews, observation, and document. The study involved one key informant and six main informants. The data were analysed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings show that women allocate their time from early morning to complete domestic responsibilities before engaging in productive work in cocoa plantations. Women also remain actively involved in social and community activities. Their contribution extends beyond generating additional household income. They manage family finances, provide childcare, and implement survival strategies to maintain household stability. Based on these results, it is concluded that women can allocate time and play a role in maintaining stability and sustainability in family economic resilience.